Jogos computacionais no ensino técnico profissional do Instituto Federal Farroupilha: panorama e possibilidades - Silva, André Hellvig da (2015)
This paper assumes that the student may be motivated to seek knowledge through various mechanisms, and many include the challenge and the joy of accomplishment as a strategy, which is known as a reward paradigm. This research aims to detect the current level of use of computer games as a tool for learning in vocational technical education at the Federal Institute Farroupilha (IF Farroupilha) and in a second step, analyze the potential unexplored games most cited on this. After submitting an online questionnaire to a group of teachers of IF Farroupilha, the information was analyzed, highlighting the three computer games most commonly used by them. The second part of relapsed analysis of the cognitive potential of, relating to, as a result, the characteristics of each of the analyzed games. The findings show that most teachers want to take games as an important tool in the learning process. However, point out difficulties in finding games that meet the needs related to the educational level in which they operate, indicating as necessary features to games the existence of mechanisms of adaptation to the level of knowledge shown by the user, collaborative environment, and multidisciplinary approach to content.